Traditional culinary uses, food applications, and potential health benefits of Peruvian Mesquite (Prosopis juliflora, Prosopis pallida), research advances and challenges: a review - Bohórquez-Medina, Sofía L. (2025)
Prosopis trees are leguminous plants that are frequently grown in arid, semiarid, tropical, and subtropical locations due to their remarkable capacity to withstand harsh soil conditions. Compared to other leguminous plants, Prosopis species are still neglected despite their promise. Prosopis juliflora (P. juliflora) and Prosopis pallida (P. pallida) are both referred to as “Mesquite” or “Algarrobo” in Peru. The purpose of this systematic literature review is to clarify the dietary benefits and food applications of Prosopis species (P. juliflora and P. pallida). A systematic search for relevant articles was conducted on SCOPUS, PubMed/Medline, and WOS. The literature review revealed that Mesquite products have been used in a variety of industries, such as construction, food, and medicine. However, their medicinal use has not been evaluated in clinical trials. Most available evidence pertaining to its health benefits was concentrated on in vitro and in vivo experimental studies. Due to its substantial fiber, protein, and polyphenol content, its nutritional value as a partial replacement for wheat flour and for boosting the nutritional profile of baked goods, drinks, and other food items is being investigated. Further research is required to fully explore food applications and nutritional potential benefits of these neglected leguminous plants.